2003
DOI: 10.1074/jbc.m305544200
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Nitroxyl and Hydroxyl Radical in Solutions of Sodium Trioxodinitrate

Abstract: Despite its negative redox potential, nitroxyl (HNO) can trigger reactions of oxidation. Mechanistically, these reactions were suggested to occur with the intermediate formation of either hydroxyl radical ( ⅐ OH) or peroxynitrite (ONOO ؊ ). In this work, we present further experimental evidence that HNO can generate ⅐ OH. Sodium trioxodinitrate (Na 2 N 2 O 3 ), a commonly used donor of HNO, oxidized phenol and Me 2 SO to benzene diols and ⅐ CH 3 , respectively. The oxidation of Me 2 SO was O 2 -independent, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 67 publications
4
24
0
Order By: Relevance
“…The possibility exists for AS to generate the hydroxyl radical ( · OH) under certain extreme biochemical conditions (9, 10). Therefore, we examined the effect of acute hydroxyl radical exposure on isolated rat cardiomyocyte function.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The possibility exists for AS to generate the hydroxyl radical ( · OH) under certain extreme biochemical conditions (9, 10). Therefore, we examined the effect of acute hydroxyl radical exposure on isolated rat cardiomyocyte function.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated hydroxyl radical production using very high concentrations of AS (>1 mmol/L) under conditions of very low pH (pH 4–6) (9, 10). Although hydroxyl radical production is minimal under our experimental conditions at pH 7.4, hydroxyl radical production may occur in certain intracellular compartments of low pH (i.e., mitochondria).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemistry responsible for these oxidation processes is not established but has been proposed to be due to several possible reactions. For example, Angeli's salt-derived HNO is proposed to be toxic to cells via the dimerization to hyponitrous acid (HONNOH) followed by a proton-dependent decomposition to N 2 and HO• (Reactions 34 and 35) [74,75].…”
Section: Hno and Radical Chemistrymentioning
confidence: 99%
“…Interestingly, HOC, spin trapped by using a pyrroline N-oxide, was detected in a decomposing solution of Angeli's salt. [84,85] The formation of HOC from HNO was proposed to occur via an azo-type homolytic fission of cis-hyponitrous acid [Eq. (16)], a reaction initially proposed almost 40 years ago to explain a small amount of radical chain chemistry associated with the decomposition of hyponitrous acid.…”
Section: Nitroxyl Toxicity and Toxicological Chemistrymentioning
confidence: 99%